Komponen Produksi Kedelai Generasi M3 Akibat Mutasi Induksi di Tanah Salin - Florentina Kusmiyati; Sutarno Sutarno; B. Herwibawa (Seminar Nasional Lahan Suboptimal, 2019)
Kusmiyati F, Sutarno S, Herbawa B. 2019. Production of soybean M3 generation affected by induced mutation at saline soil. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 392-399. Palembang: Unsri Press.Breeding for tolerance soybean at saline soil can be carried through induced mutation.  The present study was undertaken to evaluate the effect of induced mutation by gamma rays on soybean production at third generation (M3) in saline soil  The study was conducted at saline soil in Rembang Regency – Central Java.  The materials were soybean at control treatment (0 Gy) and thirteen genotypes of third generation (M3) induced mutation by gamma rays (208 Gy, 256 Gy, 352 Gy, 400 Gy, 448 Gy, 496 Gy, 592 Gy). Parameter measured were number of pod, pod weight and number of seed.  The result based on T-test showed that genotype of BSMG-02-208-8, BSMG-02-208-9, BSMG-02-352-2, BSMG-02-448-5, BSMG-02-448-7, BSMG-02-592-9 had number of pod significantly different than at control treatment. Pod number of BSMG-02-208-8 was higher than at control. Pod weight of BSMG-02-208-8, BSMG-02-352-2, BSMG-02-448-7, BSMG-02-448-10, BSMG-02-496-2, BSMG-02-592-9 were significantly different than at control treatment. Pod weight of BSMG-02-208-8 was heavier than at control.  Genotypes of BSMG-02-208-8, BSMG-02-256-7, BSMG-02-256-10, BSMG-02-352-2, BSMG-02-448-3, BSMG-02-448-5, BSMG-02-448-7, BSMG-02-448-9, BSMG-02-496-2 dan BSMG-02-592-9 were significantly different than at control treatment.  The conclusion was genotype BSMG-02-208-8 can be used for soybean tolerance breeding at saline soil for  next generation.Keywords: gamma rays, number of pod, pod weight, seed number, tolerance